Uwagi o aktorstwie w filmach Andrzeja Wajdy - Hendrykowski, Marek (Przestrzenie Teorii, 2017)
The article is a synthetic look at Andrzej Wajda’s films in terms the context of acting and actors’ participation. As a director Wajda never created a separate ‘school’ of film acting; nevertheless, he still made a huge creative contribution on a national and global scale, including tens, if not hundreds, of unforgettable performances from actors.